Robots in Social Research. Can Social Robots Conduct an Interview? - Sparano, Eleonora (Italian Sociological Review, 2022)
The pairing of Robots with the human species is increasingly common in everyday life and the outcomes of this relationship are the subject of numerous studies in this direction. Scientific literature shows that the relationship of empathy with Robots is much more possible, the more they resemble human beings, both in features and behavior. In the light of these considerations, the first Social Robots were designed, and are currently being tested to assist humans in carrying out a wide range of activities. The effects of this relationship between humans and non-humans are evident in the research conducted on educational robotics and support of fragile subjects, as in the case of people with autism. We intend to investigate the possible uses of robotics in the field of social sciences, considering that, in a possible scenario of a post-pandemic future, Robots could be called upon to replace interviewers in the different phases of the research, and in particular in conducting interviews. The question is whether and how Robots are able to detect emotions in the answers of the interviewees, establishing a relationship of empathy with the interlocutors. If we can agree on the possibility of a future in which Robots accompany researchers in the context of the survey, the reasoning changes when we focus on the applications of robotics within the qualitative methodological strategy.